BIOGEOCHEMISTRY OF SOILS OF THE DESERTS OF SOUTH FERGANA AND ONIONS (Allium cepa L.) (Scientific journal of the Fergana State University, 2025)
In the article, the biogeochemical characteristics of the amount of chemical elements found in the organs of common onion (Allium cepa L.) from the irrigated brown soil formed in the desert region and the vegetables grown in it were determined.